Knowledge Sharing in Sport Organizations: The Role of Social Capital - Hojjat Soltani Zarandi; Akbar Jaberi; Esmaeil Sharifian (Shahid Bahonar University of Kerman, 2021)
Knowledge management and its dimensions have an important role in the sustainable development of sport organizations; therefore, the main objective of this study was to investigate the effect of social capital components on knowledge sharing in sport and youth offices in Kerman. 193 staff in sport and youth offices in Kerman participated in this study through a total sampling approach, and completed a valid and reliable questionnaire. The findings of the research by applying structural equation modeling demonstrated that the social capital components (mutual respect and trust, participation and teamwork, social cohesion, openness to criticism, and relationship networks) had a positive and significant effect on the knowledge sharing in sport and youth offices in Kerman. According to the research findings, developing social capital and its components can play an important role in the process of knowledge sharing in sport and youth offices in Kerman.